GAMBARAN PENGETAHUAN DAN SIKAP IBU DALAM PENCEGAHAN DIARE PADA BALITA DI PUSKESMAS KALUMATA KOTA TERNATE - seli dela sulfiati; fera the; Soesanty Soesanty (Kieraha Medical Journal, 2020)
Background: Dehydration due to diarrhea can lead to death in all ages, especially in toddlers. In the city of Ternate, in 2018, 2,023 (9.7%) cases of diarrhea in children under the age of five are listed among the top 10 diseases in the Puskesmas Kalumata. High cases are due to such factors as maternal knowledge and diarrhea prevention. Therefore, researchers want to examine the description of knowledge and attitude mother’s diarrhea the prevention in children under five at the Puskesmas Kalumata Ternate City. Methode: Descriptive research with cross-sectional approach. Carried out  from December 12 to December 31, 2019, in the Puskesmas Kalumata Ternate City with the method used was to discharge the questionnaire by interview. The sampling technique used is an accidental sampling. Result: The result showed that among of 55 respondent, mother’s with good knowledge are 52 people (94.5%), mother’s with a good attitude are 51 people (92.7%), the age majority were 20-35 years old are 36 people (65.5%), a high level of mothers graduate from senior high school are 30 people (54,4%), most were housewife are 43 people (78.2%), and the mothers of the most children who have a child are 20 people (40.0%). Conclusion: The conclusion is that 90% of the respondents at the Puskesmas Kalumata Ternate City are capable of preventing diarrhea in toddlers. Keywords: Attitude, Children Under Five, Diarrhea Prevention, Knowledge